INTEGRATIVE STUDY OF LANGUAGE RULES IN THE PROCESS OF TEACHING JUNIOR SCHOOLCHILDREN THE AZERBAIJANI LANGUAGE - Nabat Jafarova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2024)
The morphology of the Azerbaijani language has a wide range, so the question arises about the introduction of grammatical and lexical system of language rules. The relevance of the study is determined by the need to update the means of teaching junior high school students the rules of the language in Azerbaijani language lessons. The article is designed to reveal the features of grammatical and lexical structure and a comprehensive study of the language norms of the Azerbaijani language for elementary school students. The article aimed to describe grammatical and lexical features and their expression during students’ integrative learning of language rules. For this, the research used the methods of analysis, synthesis, comparison, deduction, generalisation, and a pedagogical experiment. The deductive method played a crucial role in this study, revealing unique aspects of the child’s lexical and grammatical mastery. This was achieved by using common knowledge related to education and language capabilities. Deduction was important for the formulation of distinctive features and characteristics that should be taken into account by teachers when teaching the Azerbaijani language. In addition, the article uses the method of generalization to prepare exercises for schoolchildren from a wide range of educational subjects. This approach involved incorporating the theoretical ideas explored in the study into the content of the exercise. The aim was not only to introduce these concepts but also to reinforce their understanding of the tasks, thus assessing the degree of students’ understanding and mastery. This approach enriches the educational process, ensuring the effective implementation of theoretical knowledge in practical learning experience. As a result of the work, it was established that the comprehensive study of language rules from morphology involved increasing the level of student’s knowledge, namely their conscious understanding of words in the process of speaking. Therefore, the main areas of the formation of speaking abilities and skills of younger schoolchildren are revealed. The article proves that this process is closely related to the increase in vocabulary, which, in turn, is an indicator of the richness of the language. The study presents a structured approach to teaching Azerbaijani language to junior high school students, focusing on morphological analysis, suffix exercises, and the interrelation of grammatical and lexical features. It emphasizes integrating these aspects to enhance students’ understanding and use of language. Key findings demonstrate the effectiveness of this integrative method in improving vocabulary, speech culture, and overall linguistic competence.